2013
DOI: 10.1002/hed.23279
|View full text |Cite
|
Sign up to set email alerts
|

Transoral laser microsurgery followed by radiation therapy for oropharyngeal tumors: The mayo clinic arizona experience

Abstract: Background The purpose of this study was to report the treatment outcomes of patients with advanced oropharyngeal cancer treated with transoral laser microsurgery (TLM) followed by radiation therapy (RT) at Mayo Clinic in Arizona. Methods A retrospective study of 80 patients treated from January 1, 2000 to November 7, 2011 was performed. All patients had stage III/IV oropharyngeal tumors and underwent TLM with neck dissection. Adjuvant RT was then given. Thirty-seven patients received concurrent adjuvant che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
(35 reference statements)
6
11
0
Order By: Relevance
“…To this end, there is an ongoing effort in our department to incorporate routine measurement of an array of both subjective and objective swallowing evaluations as part of our standard minimum dataset. Congruous results have also been observed in previous TLM series with similarly high rates of HPV positivity in which only a minority of patients were treated with adjuvant CRT, 9,13,[30][31][32][33] albeit a greater proportion than in the present series. 40,41 In a nonrandomized, case-matched study of patients treated for advanced oropharyngeal SCC with either CRT or TLM, O'Hara et al 40 observed significantly better swallowing scores for the TLM cohort at 3 months after treatment, as assessed with patient-reported outcomes using the MD Anderson Dysphagia Inventory, clinicianrated dietary texture restrictions using the Normalcy of Diet scale, and objective swallow performance using the timed Water Swallow Test.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…To this end, there is an ongoing effort in our department to incorporate routine measurement of an array of both subjective and objective swallowing evaluations as part of our standard minimum dataset. Congruous results have also been observed in previous TLM series with similarly high rates of HPV positivity in which only a minority of patients were treated with adjuvant CRT, 9,13,[30][31][32][33] albeit a greater proportion than in the present series. 40,41 In a nonrandomized, case-matched study of patients treated for advanced oropharyngeal SCC with either CRT or TLM, O'Hara et al 40 observed significantly better swallowing scores for the TLM cohort at 3 months after treatment, as assessed with patient-reported outcomes using the MD Anderson Dysphagia Inventory, clinicianrated dietary texture restrictions using the Normalcy of Diet scale, and objective swallow performance using the timed Water Swallow Test.…”
Section: Discussionsupporting
confidence: 79%
“…31 Similar oncological outcomes have been reported in three US single-center series, 13,32,33 with particularly propitious results reported in a recent appraisal of 80 patients with advanced oropharyngeal SCC, albeit predominantly low T classification, from the Mayo Clinic Arizona: respective 3-year locoregional control, DFS, and OS estimates were 98.6%, 91.1%, and 93.7%, respectively. For our study cohort as a whole, 81.0% of which comprised stage III or IV disease, we observed a 3-year locoregional control rate of 89.6% and, respective, 3-year OS, DSS, and DFS rates of 84.5%, 91.7%, and 78.2%, which, although challenging to compare with the oncologic outcomes from previous contemporary surgical series owing to varying distributions of disease stage, HPV status, and adjuvant therapy strategy, seem broadly consistent.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The majority of patients (73%) had adjuvant therapy. Other authors have also confirmed excellent survival following TLM of OPSCCA, with 2‐year DSS over 90% . The frequent presence of nodal metastases results in advanced stage (III or IV) in the majority of patients, and often results in the adjuvant delivery of chemotherapy and radiation to these patients as well as the initial surgery.…”
Section: Introductionmentioning
confidence: 80%
“…Patel and colleagues 1 are to be congratulated for demonstrating excellent outcomes in their patients treated with TLM and adjuvant therapy. However, it is important to stress that the conclusion should have read “TLM followed by RT for selected patients with advanced oropharyngeal cancer results in excellent control rates”, as this retrospective study has clear selection bias.…”
mentioning
confidence: 99%